Downregulation of Cytokines and Chemokines by GB Virus C After Transmission Via Blood Transfusion in HIV-Positive Blood Recipients. (25th November 2014) - Lanteri, Marion C.; Vahidnia, Farnaz; Tan, Sylvia; Stapleton, Jack T.; Norris, Philip J.; Heitman, John; Deng, Xutao; Keating, Sheila M.; Brambilla, Don; Busch, Michael P.; Custer, Brian; ,; et al.
Abstract: Background.  An association between GB virus C (GBV-C) and improved outcomes of human immunodeficiency virus (HIV) infection has been reported in HIV-positive individuals with active GBV-C coinfection. This study provides insights into the immune mechanisms underlying the protective role of GBV-C in HIV-infected patients. Methods.  The concentrations of 64 cytokines and chemokines were measured in plasma samples obtained from the Viral Activation Transfusion Study cohort before transfusion and longitudinally from 30 patients positive for both HIV and GBV-C (hereafter, "cases") and 30 patients positive for HIV and negative for GBV-C (hereafter, "controls"). Results.  Cases had lower HIV viral loads and higher CD4 T-cell counts than controls after acquisition of GBV-C infection. Most of the modulated cytokines and chemokines were reduced after GBV-C detection, including many proinflammatory cytokines, suggesting an overall antiinflammatory effect of GBV-C in HIV-positive subjects. Most pathways and functions of the measured cytokines were downregulated in cases, except cell death pathways, which were upregulated in various cell subsets in the 3 months after GBV-C detection. Conclusions.  GBV-C has a protective effect, in part through a competition mechanism leading to decreased inflammation and improved HIV disease outcome in cases. Further studies are necessary to establish whether GBV-C may have deleterious effects on the host at the cellular level, including depleting the cells that are the targets of HIV.